2002
DOI: 10.1093/brain/awf068
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline prevents neurotoxicity induced by cerebrospinal fluid from patients with motor neurone disease

Abstract: CSF from patients with motor neurone disease (MND) has been reported to be toxic to cultured primary neurones. We found that CSF from MND patients homozygous for the D90A CuZn-superoxide dismutase (CuZn-SOD) mutation, patients with sporadic MND and patients with familial MND without CuZn-SOD mutations significantly increased apoptosis and reduced phosphorylation of neurofilaments in cultured spinal cord neurones when compared with the effects of CSF from patients with other neurological diseases. Exposure of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 75 publications
2
79
1
1
Order By: Relevance
“…In contrast to these findings, others have also demonstrated similar glutamate levels in CSF from patients with ALS and controls [83,84]. Interestingly, another study shows lower levels of glutamate in the CSF that fails to correlate to disease progression or decreased MN cell death [85]. However, measurements of CSF concentrations of glutamate in response to therapeutics remains to be explored and therefore further investigation is warranted.…”
Section: Metabolic Biomarkersmentioning
confidence: 91%
“…In contrast to these findings, others have also demonstrated similar glutamate levels in CSF from patients with ALS and controls [83,84]. Interestingly, another study shows lower levels of glutamate in the CSF that fails to correlate to disease progression or decreased MN cell death [85]. However, measurements of CSF concentrations of glutamate in response to therapeutics remains to be explored and therefore further investigation is warranted.…”
Section: Metabolic Biomarkersmentioning
confidence: 91%
“…Minocycline has been shown to have a neuroprotective effect in animal models of other neurologic conditions such as multiple sclerosis (MS), 33,34 Parkinson disease, 11 Huntington disease, 35,36 amyotrophic lateral sclerosis (ALS), 36,37 and traumatic brain disease. 10,38 In some of these conditions, minocycline has had a therapeutic benefit in clinical trials.…”
Section: Statistical Methods For the Primary Analysis An Intention-mentioning
confidence: 99%
“…Similar findings were reported by Kriz et al (2002) and Van Den Bosch et al (2002), who showed that minocycline delayed the onset of motor neuron degeneration and muscle strength decline and increased the longevity of amyotrophic lateral sclerosis mice. Additional in vitro studies revealed that minocycline reduced the apoptosis of cultured neurons from patients with motor neuron diseases, including amyotrophic lateral sclerosis (Tikka et al, 2002). As is the case for Huntington's and Parkinson's diseases, the usefulness of minocycline in this neurological condition remains controversial, however.…”
Section: Effects Of Minocycline On Cns Pathologiesmentioning
confidence: 99%